A history of canine parvovirus in Australia: what can we learn?. Issue 10 (4th August 2020) - Kelman, M; Norris, JM; Barrs, VR; Ward, MP
Abstract : Canine parvovirus (CPV) has been reported throughout the world since the late 1970s. Published information was reviewed to draw insights into the epidemiology, pathogenesis, diagnosis, treatment and outcomes of CPV disease in Australia and the role of scientific research on CPV occurrence, with key research discoveries and knowledge gaps identified. Australian researchers contributed substantially to early findings, including the first reported cases of parvoviral myocarditis, investigations into disease aetiopathogenesis, host and environmental risk factors and links between CPV and feline panleukopenia. Two of the world's first CPV serological surveys were conducted in Australia and a 1980 national veterinary survey of Australian and New Zealand dogs revealed 6824 suspected CPV cases and 1058 deaths. In 2010, an Australian national disease surveillance system was launched; 4940 CPV cases were reported between 2009 and 2014, although underreporting was likely. A 2017 study estimated national incidence to be 4.12 cases per 1000 dogs, and an annual case load of 20, 110 based on 4219 CPV case reports in a survey of all Australian veterinary clinics, with a 23.5% response rate. CPV disease risk factors identified included socioeconomic disadvantage, geographical location (rural/remote), season (summer) and rainfall (recent rain and longer dry periods both increasing risk). Age <16 weeks was identified as a risk factor for vaccination failure. Important knowledge gaps exist regarding national canine and feline demographic and CPV case data, vaccination coverage and population immunity, CPV transmission between owned dogs and other carnivore populations in Australia and the most effective methods to control epizootics.